Medical Vulnerability in America: How Does the Health System Respond? - James R. Knickman; Kelly A. Hunt (SAGE Publishing, 2003)
This study explores the hypothesis that market change affects the medically vulnerable more than the non-medically vulnerable. Analysis of data measuring change between 1997 and 1999 indicates that access to care eroded for both groups, but no evidence emerges to suggest that the changes were systematically worse for the medically vulnerable. Paradoxically, some measures of satisfaction with actual care received improved between 1997 and 1999 for both groups of people. Recent market changes do not seem to pose extra special threats to the medically vulnerable. However, our findings reinforce the need to better coordinate and integrate services for the medically vulnerable and chronically ill.